1, 25(OH)2D3 improves cardiac dysfunction, hypertrophy, and fibrosis through PARP1/SIRT1/mTOR‐related mechanisms in type 1 diabetes. Issue 5 (10th October 2016) - Qu, Hua; Lin, Ke; Wang, Hang; Wei, Huili; Ji, Baolan; Yang, Zengsong; Peng, Chuan; Xiao, Xiaoqiu; Deng, Huacong
Abstract : This study focusses on the cardiac protecting role of 1, 25(OH)2 D3 and its potential mechanisms. 1, 25(OH)2 D3 ‐treatment can improve the cardiac function and structure, and interstitial fibrosis in type 1 diabetic rat, while VDR silencing reverses these effects. 1, 25(OH)2 D3 ‐VDR signaling induces this protective effect on diabetic cardiomyopathy might partly through the PARP1/SIRT1/mTOR pathway. Abstract : Scope: Diabetic cardiomyopathy is one of the most important cardiac complications associated with diabetes. However, the mechanisms underlying diabetic cardiomyopathy remain unclear. The PARP1, SIRT1, and mTOR pathways have been implicated in cardiac diseases, and they are also associated with diabetes. 1, 25(OH)2 D3 was recently recognized as a potential PARP1inhibitor in a macrophage cell line. The aim of our study was to investigate whether 1, 25(OH)2 D3 can improve diabetic cardiomyopathy through a vitamin D receptor (VDR)‐dependent mechanism associated with the PARP1/SIRT1/mTOR pathway. Methods and results: 1, 25(OH)2 D3 ‐treated diabetic rats displayed improved left ventricular wall thickness and end‐diastolic/systolic diameter, end‐diastolic/systolic volume, left ventricular ejection fraction, fractional shortening, atrial natriuretic peptide, and brain natriuretic peptide gene expression, and interstitial fibrosis compared with untreated diabetic rats, while silencing the VDR gene in DM rats blocked the above results. 1, 25(OH)2 D3 treatment also decreased PARP1 and increased SIRT1 expression levels and repressed the phosphorylation of mTOR. Treating neonatal cardiomyocytes with 1, 25(OH)2 D3 and a PARP1 inhibitor decreased PARP1 and increased SIRT1 protein expression. Conclusion: The present study demonstrates that 1, 25(OH)2 D3 treatment has the potential to improve diabetic cardiomyopathy in rats and suggests that VD‐VDR signaling induces this protective effect against diabetic cardiomyopathy might partly through the PARP1/SIRT1/mTOR pathway.